2021
DOI: 10.18632/aging.202902
|View full text |Cite
|
Sign up to set email alerts
|

Does taking an angiotensin inhibitor increase the risk for COVID-19? – a systematic review and meta-analysis

Abstract: Because SARS-COV2 entry into cells is dependent on angiotensin converting enzyme 2 (ACE2) and angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) increase ACE2 activity, the safety of ACEI/ARB usage during the coronavirus disease 2019 (COVID-19) pandemic is a controversial topic. To address that issue, we performed a meta-analysis following The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Searches of the Embase, MEDLINE, PubMed, and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
1
9
0
1
Order By: Relevance
“…Another study reported that ARBs were associated with reduced mortality in elderly patients with SARS‐CoV‐2 with type 2 diabetes mellitus, though curiously, this was not the case for ACEIs 15 . In contrast, some studies do not support an association between ACEIs/ARBs and negative outcomes 12,13,21–23 . Notably, a recent randomized, open‐label trial in which patients were randomly assigned to either continue or discontinue ACEI/ARB use did not support an association between stopping ACEIs/ARBs and negative outcomes 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that ARBs were associated with reduced mortality in elderly patients with SARS‐CoV‐2 with type 2 diabetes mellitus, though curiously, this was not the case for ACEIs 15 . In contrast, some studies do not support an association between ACEIs/ARBs and negative outcomes 12,13,21–23 . Notably, a recent randomized, open‐label trial in which patients were randomly assigned to either continue or discontinue ACEI/ARB use did not support an association between stopping ACEIs/ARBs and negative outcomes 22 .…”
Section: Discussionmentioning
confidence: 99%
“…15 In contrast, some studies do not support an association between ACEIs/ARBs and negative outcomes. 12,13,[21][22][23] Notably, a recent randomized, open-label trial in which patients were randomly assigned to either continue or discontinue ACEI/ARB use did not support an association between stopping ACEIs/ARBs and negative outcomes. 22 However, this study was relatively small (n = 152) and ACEI/ARB use was changed only after infection.…”
Section: Discussionmentioning
confidence: 99%
“…These differences likely contributed to the conflicting findings between this and similar studies. Many analyses have found no significant difference in either COVID-19 severity or mortality related to ACEI/ARB prescription [ 55 , 56 , 58 , 61 ] whilst others have found significant reductions either for the whole population [ 54 , 57 , 62 ] or in sub-analyses, such as for patients with hypertension [ 59 , 60 ]. No studies have found an increased risk of severe disease or mortality from COVID-19 in relation to ACEI/ARB prescription.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have found an increased risk of severe disease or mortality from COVID-19 in relation to ACEI/ARB prescription. Some analyses also examined the association between ACEI/ARB prescription and the risk of COVID-19 infection, which also varied depending on the class of agent (significant reduction with ACEI but not ARB) [ 57 ], and sub-analyses of the patient population (significant increase but not when adjusting for patients with hypertension) [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation